2016
DOI: 10.1007/s11104-016-3089-5
|View full text |Cite|
|
Sign up to set email alerts
|

Diel plant water use and competitive soil cation exchange interact to enhance NH4 + and K+ availability in the rhizosphere

Abstract: Aims Hydro-biogeochemical processes in the rhizosphere regulate nutrient and water availability, and thus ecosystem productivity. We hypothesized that two such processes often neglected in rhizosphere models -diel plant water use and competitive cation exchangecould interact to enhance availability of K + and NH , Na + ) to desorb NH 4 + and K + from soil, generating non-monotonic dissolved concentration profiles (i.e. 'hotspots' 0.1-1 cm from the root). Cation accumulation and competitive desorption increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 63 publications
0
18
1
1
Order By: Relevance
“…Rhizosphere oxygen concentration also likely follows a diel pattern that could partially control the activity of rhizosphere-associated microbes (42). Modeling efforts suggest that diel changes in water flow through the rhizosphere (43) would have a big impact on oxygen concentration. Active root and microbial growth in the rhizosphere may also create oxygen depletion zones within the rhizosphere (44).…”
Section: Figmentioning
confidence: 99%
“…Rhizosphere oxygen concentration also likely follows a diel pattern that could partially control the activity of rhizosphere-associated microbes (42). Modeling efforts suggest that diel changes in water flow through the rhizosphere (43) would have a big impact on oxygen concentration. Active root and microbial growth in the rhizosphere may also create oxygen depletion zones within the rhizosphere (44).…”
Section: Figmentioning
confidence: 99%
“…The root uptake of nutrient is assumed to be an active uptake process as opposed to a passive process where solutes are simply taken up with the porewater by the roots. The active uptake rate is represented by a Michaelis-Menten expression (Somma et al 1998;Wu et al 2007;Espeleta et al 2017) in this model as shown in the following equation:…”
Section: Root Water Uptake Modelmentioning
confidence: 99%
“…Using a simple 1D model given prescribed water potential at soil-root boundary, Espeleta et al (2017) found that competitive cation exchange enabled NH 4 + and K + from soil to be desorbed from soil exchange sites and made available for plant use when low-demand cations such as Ca 2+ , Mg 2+ , and Na + accumulated near roots during water uptake. To simulate competitive ion exchange in 3D, cation exchange reactions (Table 1) and root nutrient uptake were included in our model.…”
Section: Competitive Cation Exchangementioning
confidence: 99%
See 2 more Smart Citations